Shame, Chronic Illness and Participatory Storytelling. (December 2022) - Stage, Carsten
The article explores the complex roles shame plays in the lives of people with one or more chronic conditions. This is achieved through a participatory research process in which people with chronic conditions were invited to share stories of shame on the public social media profiles of a peer-led patient community called 'Chronic Influencers'. The crowdsourced material shows that 7 out of 10 experience shame in relation to their illness on a daily or weekly basis. Other findings are that shame seems to stick to 'energetic failures' of the slow or tired body in various social situations; shame is predominantly produced or anticipated in the intimate sphere; and shame can be 'rescripted' as culturally produced and politically contestable – and thus counter the pressure to individualise health as a project of personal improvement and self-inspection – when it is shared through voluntary storytelling among peers on social media.